Localism and centralism in Europe the political and legal bases of local self-government - Page, Edward (Oxford Oxford University Press, 1991)
A study of the legal and political basis of relationships between national and local government in Britain, France Norway, Sweden, Denmark, Italy and Spain. The author examines the differences between these countries and their implications for patterns of policy-making at local level.
Keywords: Central-local government relations -- Europe; Local government -- Law and legislation -- Europe; Comparative government